Connecting morphology and photoluminescence emissions in β-Ag2MoO4 microcrystals. Issue 3 (1st February 2022) - Teodoro, Vinícius; Gouveia, Amanda Fernandes; Machado, Thales Rafael; Trench, Aline Barrios; Jacomaci, Natalia; Assis, Marcelo; Marques, Gilmar Eugenio; Teodoro, Marcio Daldin; San-Miguel, Miguel Angel; Andrés, Juan; Bettini, Jefferson; Longo, Elson
Abstract: This work elucidates the morphology-photoluminescence (PL) emission relationships, based on experimental and calculated results, on β-Ag2 MoO4 samples synthesized by microwave-assisted hydrothermal method. It was shown that the solvent (water and ammonia) and temperature (120, 130, 140, and 150 °C) play a crucial role in the morphology and PL emissions. A crystal structure model, composed by the local coordination of both Ag and Mo atoms at bulk and exposed surfaces, was built, and the possible mechanism along the synthesis progress was proposed and analyzed. This study provides an idea for the preparation and development of β-Ag2 MoO4 based materials with desirable properties.